Upper-Body Muscular Endurance and Its Association with Aerobic Capacity in University Students of Physical Culture, Sport, and Recreation - Rangel Caballero, Luis Gabriel; García Mantilla, Ezequiel David; Murillo López, Alba Liliana; Pérez Bernal, Manuel Alejandro; Irribarren Llorente, Lourdes Luz (MHSalud: Revista en Ciencias del Movimiento Humano y Salud, 2024)
Introduction: Upper-body muscular endurance (UBME) and aerobic capacity (AC) are essential components of physical fitness. Low levels of these components are related to cardiovascular disease. Purpose: To assess the association between UBME and AC levels in college students of physical culture. Methodology: Analytical cross-sectional study carried out in 192 students (169 men, 23 women; median age 20 years). Every participant of the study signed written consent. UMBE was the dependent variable assessed by the push-up test, and AC was the main independent variable assessed using the 20 m shuttle run test. To analyze differences by sex, and academic semester, Fischer exact, Student’s T, and U Mann-Whitney tests were applied. Descriptive, as well as bivariate and multivariate analysis, were realized using logistic regression models. Results: 82.29 % of participants had healthy levels of UBME. Respecting the academic semester, students had a higher probability of having healthy levels of UBME as semesters increased (OR: 1.23, 95 % CI: 1.06 to 1.44, p = 0.007). Concerning AC, 58.33 % of participants registered healthy levels. After adjusting by sex, age, socioeconomic level, and academic semester, maximum oxygen consumption (VO2max), was associated with healthy levels of UBME (OR: 1.157, CI 95 %: 1.O71 – 1.249, p=<0.001). Conclusions: Students had a higher probability of presenting healthy levels of UBME as semesters of study increased, and those with a higheVO2max were more likely to have healthy levels of UBME.